Analisis Perceived Value Terhadap Loyalitas Muzakki dalam Perspektif Akuntansi Syariah pada Entitas Syariah Nonbank - Dwi Arieska; Andi Rezky Adzarani T; Alfiah Alfiah; Masyhuri Masyhuri (INDO PUBLISHING, 2026)
This study discusses the role of perceived value in building muzakki loyalty in non-bank Islamic entities through the perspective of Islamic accounting. Muzakki loyalty is an important factor in maintaining the sustainability of zakat management institutions because it is related to public trust in the management of zakat funds. This study uses a qualitative approach with a library research method based on scientific journals, books, and previous studies relevant to the research topic. The data analysis technique was carried out by reviewing and interpreting various scientific sources systematically. The results show that service quality, transparency, accountability, service convenience, and the implementation of sharia principles are able to create positive perceived value and increase muzakki loyalty. From the perspective of Islamic accounting, the principles of trustworthiness, fairness, transparency, and responsibility become important foundations in building muzakki trust toward zakat management institutions. This study indicates that muzakki loyalty is influenced not only by service quality, but also by trust in the institution’s integrity in implementing sharia values consistently.